The impact of pathological fractures on therapy outcome in patients with primary malignant bone tumours - Moradi, Babak; Zahlten-Hinguranage, Anita; Lehner, Burkhard; Zeifang, Felix (International orthopaedics, 2010)
The primary objective of this study was to investigate the implications of pathological fractures on therapy outcome in patients with primary malignant bone tumours and to determine whether limb salvage can be safely performed. A retrospective analysis of 447 patients with primary malignant bone tumours, treated between 1985 and 2005, was performed. Multivariate Cox regression analysis was used to investigate the influence of pathological fractures and further independent variables on survival rate. In 52 of the 447 patients, the primary malignant bone tumour was complicated by a pathological fracture. These fractures were more common in malignant fibrous histiocytoma (MFH) of the bone and in the tumour stages IIa/b and III. Ablative surgery was performed in ten patients and limb salvage surgery in 42 patients. The mortality risk for patients with pathological fractures was significantly increased by a factor of 1.82 (p = 0.015), and overall duration of survival was significantly lower in the fracture group, with a median of 6.2 years (p < 0.00001). In univariate and multivariate analysis, fracture, higher tumour stages and resection margins remained a significant predictor of worse survival. Overall survival, rate of local recurrence and distant metastases were not affected by the type of surgical treatment selected; there was no difference between the patients who underwent limb salvage and those who underwent an amputation. Pathological fracture in patients with primary malignant bone tumours is a predictor of worse survival and significantly increases mortality risk. Reconstructive surgery did not influence the survival rate, showing that limb salvage therapy is safe when adequate resection margins are achieved.
Erstmals am 13. Dezember 2009 online veröffentlicht
Gesehen am 03.05.2023